Treatment strategies for early stage hepatocellular carcinoma: a systematic review and network meta-analysis of randomised clinical trials. Issue 4 (April 2021) - Kamarajah, Sivesh K.; Bundred, James R.; Littler, Peter; Reeves, Helen; Manas, Derek M.; White, Steven A.
Abstract: Background: Several treatment strategies for early stage hepatocellular cancers (HCC) have been evaluated in randomised controlled trials (RCTs). This network meta-analysis (NMA) aimed to explore the relative effectiveness of these different approaches on their impact on overall (OS) and recurrence-free survival (RFS). Methods: A systematic review was conducted to identify RCT's reported up to 23rd January 2020. Indirect comparisons of all regimens were simultaneously compared using random-effects NMA. Results: Twenty-eight RCT's, involving 3, 618 patients, reporting 13 different treatment strategies for early stage HCC were identified. Median follow-up, reported in 22 studies, ranged from 12–93 months. In this NMA, RFA in combination with iodine-125 was ranked first for both RFS (HR: 0.50, 95% CI: 0.19–1.31) and OS (HR: 0.41, 95% CI: 0.19–0.94). In subgroup with solitary HCC, lack of studies reporting RFS precluded reliable analysis. However, RFA in combination with iodine-125 was associated with markedly better OS (HR: 0.21, 95% CI: 0.05–0.93). Conclusion: This NMA identified RFA in combination with iodine-125 as a treatment delivering better RFS and OS, in patients with early stage HCC, especially for those with solitary HCC. This technique warrants further evaluation in both Asia and Western regions.